Superoxide Dismutase 3 Limits Collagen-Induced Arthritis in the Absence of Phagocyte Oxidative Burst. (10th January 2012) - Kelkka, Tiina; Laurila, Juha Petteri; Sareila, Outi; Olofsson, Peter; Laukkanen, Mikko Olavi; Holmdahl, Rikard
Abstract : Extracellular superoxide dismutase (SOD3), an enzyme mediating dismutation of superoxide into hydrogen peroxide, has been shown to reduce inflammation by inhibiting macrophage migration into injured tissues. In inflamed tissues, superoxide is produced by the phagocytic NOX2 complex, which consists of the catalytic subunit NOX2 and several regulatory subunits (e.g., NCF1). To analyze whether SOD3 can regulate inflammation in the absence of functional NOX2 complex, we injected an adenoviral vector overexpressing SOD3 directly into the arthritic paws of Ncf1 */* mice with collagen-induced arthritis. SOD3 reduced arthritis severity in both oxidative burst-deficient Ncf1 */* mice and also in wild-type mice. The NOX2 complex independent anti-inflammatory effect of SOD3 was further characterized in peritonitis, and SOD3 was found to reduce macrophage infiltration independently of NOX2 complex functionality. We conclude that the SOD3-mediated anti-inflammatory effect on arthritis and peritonitis operates independently of NOX2 complex derived oxidative burst.